PSAK-71 and Firm Value: Mediating Role of Allowance for Bad Debt and Profitability - Yolanda Aryanti; Tri Lestari; Agus Sholikhan Yulianto (AKUNTABILITAS, 2023)
This study invetigates the effect of the implementation of PSAK 71 on firm value with profitability as an intervening variable. The population of this study is banking companies listed on the Indonesia Stock Exchange for the period 2018-2021. Determination of the sample using purposive sampling and selected 17 companies. The result shows a direct positive influence of PSAK 71 on AFBD and PSAK 71 on ROA. The analysis also uncovers the negative impact of AFBD on ROA, AFBD on PBV and ROA on PBV. Meanwhile, this research does not find any influence of PSAK 71 on PBV. Sobel tests prove the negative partial mediation role of AFBD on the impact of PSAK 71 on ROA and ROA in the effect of AFBD and PBV. On the other hand, we also find the full negative mediation role of AFBD on the influence of PSAK 71 on PBV and ROA on the effect of PSAK 71 on PBV.